The Influence Of Employee Leadership And Discipline On Improving Service Qualityto The Community At The Village Officedwitiro Bontotiro District Bulukumba District - Siswan, Siswan; Ahmad, Ahmad; Samsul Rizal (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to analyze the extent of the influence of employee leadership and discipline on improving the quality of community services at the Dwitiro Village Office, Bontotiro District, Bulukumba Regency.